1999
DOI: 10.1093/clinchem/45.2.165
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic and Clinical Aspects of Noninvasive Glucose Measurements

Abstract: Frequent determination of glucose concentrations in diabetic patients is an important tool for diabetes management. This requires repetitive lancing and finger bleeding. Use of noninvasive (NI) detection techniques offers several advantages, such as the absence of pain and exposure to sharp objects and biohazard materials, the potential for increased frequency of testing, and hence, tighter control of the glucose concentrations, and the potential for a closed-loop system including a monitor and an insulin pump… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
116
0
6

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 296 publications
(124 citation statements)
references
References 85 publications
2
116
0
6
Order By: Relevance
“…The overtone band contains an absorption peak at 1688 nm originated 2 of -CH, and the combination band has absorption peaks at 2261 and 2326 nm that are the combinations of a CH stretch and a CCH, OCH deformation, respectively. 13 The calibration and prediction results were analyzed in terms of the standard error of cross validation ͑SECV͒, standard error of calibration ͑SEC͒, standard error of prediction ͑SEP͒, and regression coefficient of prediction ͑R pred ͒. On day 1, 21 samples of 7 glucose levels and 3 intralipid concentrations were made and their reflectance and transmittance spectra were measured.…”
Section: Resultsmentioning
confidence: 99%
“…The overtone band contains an absorption peak at 1688 nm originated 2 of -CH, and the combination band has absorption peaks at 2261 and 2326 nm that are the combinations of a CH stretch and a CCH, OCH deformation, respectively. 13 The calibration and prediction results were analyzed in terms of the standard error of cross validation ͑SECV͒, standard error of calibration ͑SEC͒, standard error of prediction ͑SEP͒, and regression coefficient of prediction ͑R pred ͒. On day 1, 21 samples of 7 glucose levels and 3 intralipid concentrations were made and their reflectance and transmittance spectra were measured.…”
Section: Resultsmentioning
confidence: 99%
“…Raman spectroscopy is a well-known optical spectroscopic technique that gives a large amount of information about the molecular structure and chemical environment of the sample. It has been used in many applications in the field of biology, chemistry and food, pharma and oil industries [1][2][3][4][5][6]. The conventional Raman spectroscopy is based on a CW laser and a CCD detector, and unfortunately both the Raman scattered and fluorescence induced photons are collected.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has been demonstrated that frequent monitoring of blood glucose level in diabetic patients, followed by administering a proper dose of insulin to maintain the blood glucose level in the healthy range (i.e. 70–130 mg/dL) can reduce the overall medical care costs, and delay the onset of serious complications . Additionally, continuous glucose monitoring is critical for patients with hypoglycaemia, a medical condition which occurs in diabetic patients if the release of glucose into the bloodstream is either too slow or too much insulin is released into the blood stream .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, such spectroscopic measurements should be able to produce reliable glucose measurements in the interstitial fluid of the human body for a period which is long enough to justify the surgical implantation procedure. However, once implanted in the body, the sensor will be influenced by the surrounding biological environment . Such influences may include the growth of wound tissue encapsulating the sensor, and/or gradual growth of a thin tissue layer in the optical path of the sensor over time.…”
Section: Introductionmentioning
confidence: 99%